Requisitos e limites do poder geral de efetivação para aplicação de medidas executivas atípicas - Gava Filho, João Miguel (2020)
The purpose of this study is to mark off the requirements and limits of judges’ general power for the application of atypical enforcement measures, in accordance with article 139, IV, of the Civil Procedure Code of 2015.Therefore, firstly, the basic premises that support the meaning and reach of the general power of effectiveness are presented. Other items that followed are: what was done through: the delimitation of the judicial enforcement protection, the presentation of the existing enforcement techniques within the legal order, the demonstration of the evolution of that protection modality in civil proceedings represented by overcoming the principle of typicality, detailing the general enforcement clauses found in Code of Civil Procedure of 2015 and, finally, through research on mitigation of the principle of penalties within the scope of enforcement protection. Then, a jurisprudential research in the Superior Court of Justice and in the Court of Justice of the State of São Paulo on the application of article 139, IV, of the Civil Procedure Code was carried out in order to retrieve the most relevant criteria for application of atypical measures for obligation to pay amounts. This was extremely relevant to reach a general criteria for application of atypical measures for all obligation classifications (pay amount, to do, not to do and to deliver a thing). Following, based on the data collected and further doctrinal examination, the constitutional, procedural and other criteria taken from the legal system were outlined. This in order to propose a systematization of the study by preparing some guidelines for testing atypical enforcement measures